(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Determine the rate of loss of blood pressure; the relationship between factors including: age, body mass index, smoking, dyslipidemia, diabetes, chronic kidney disease and antihypertensive drugs with loss of blood pressure, the relationship between loss of blood pressure with left ventricular hypertrophy, atherosclerosis and common carotid artery intima-media thickening via ultrasound in elderly men with hypertension. Method: The study design is descriptive cross-sectional. Subject: elder hypertensive men who are inpatients at Department of Senior Official in 175 Military Hospital from July 2020 to May 2021. Results: Non-dipper accounts for 85.7%. Obesity, chronic kidney disease, the use of a higher number of antihypertensive drugs and the using time of antihypertensive drug associate with non-dipper (p <0.05). And non-dipper is an independent factor of common cariotid intima-media thickness (OR = 4.39, 95% CI: 1.03 – 18.4, p = 0.045). Conclusion: Non-dipper is very common in elder hypertensive men. Obesity, chronic kidney disease, number of antihypertensive agent, the using time of antihypertensive drug relate to non-dipper. And the abnormality is an independent factor of common cariotid intima-media thickness.